Assessment of the Availability and Adequacy of Farm Inputs for Sustainable Agricultural Production in Ekiti State - O., Onipede; O. I., Lawal; E. O., Oluchi (Journal of Home Economics Research, 2024)
The main purpose of the study was to assess the availability and adequacy of farm inputs supplied to farmers by Agricultural inputs supply Agency (AISA) for sustainable Agricultural production. This study was carried out in Ekiti State. The population of the study was 800 register farmers in the three agricultural zones in Ekiti State. The sample of study was 264 selected through (33%) proportionate random sampling technique. A 24 items structured questionnaire was used to collect data for the study. It was found out that: farm inputs such as agro-chemicals, livestock feeds, improve seeds, fertilizers and farm tools were made available by Agricultural Input Supply Agency (AISA) for farmer‟s use; Storage services of AISA were inadequate. It was recommended that the state government and the administrator of AISA should improve the storage services of AISA to reduce the problem of wastage of agricultural produce in the State.